Effects of low volume isometric leg press complex training at two knee angles on force-angle relationship and rate of force development. - Bogdanis, Gregory C; Tsoukos, Athanasios; Methenitis, Spyridon K; Selima, Elisavet; Veligekas, Panagiotis; Terzis, Gerasimos (Eur J Sport Sci, 2018)
This study compared knee angle-specific neuromuscular adaptations after two low-volume isometric leg press complex training programmes performed at different muscle lengths. Fifteen young males were divided into two groups and trained three times per week for 6 weeks. One group (n = 8) performed 5-7 sets of 3 s maximum isometric leg press exercise, with 4 min recovery, with knee angle at 85° ± 2° (longer muscle-tendon unit length; L-MTU). The other group (n = 7) performed the same isometric training at a knee angle of 145° ± 2° (180°= full extension; shorter muscle-tendon unit length; S-MTU). During the recovery after each set of isometric exercise, participants performed two CMJ every minute, as a form of complex training. Maximum isometric force (MIF) and rate of force development (RFD) were measured over a wide range of knee angles. Countermovement jump (CMJ) performance and maximum half-squat strength (1RM) were also assessed. Training at S-MTU induced a large increase of MIF (22-58%, p < 0.02) and RFD (18-43%, p < 0.05 to 0.001) at knee angles close to the training angle and resulted in a 14° ± 9° shift of the force vs. knee joint angle relationship towards extended knee joint angles (p = 0.001). In contrast, training at L-MTU, resulted in a moderate and similar (≈12.3%, p = 0.028) improvement of force at all knee angles. CMJ performance and 1RM were equally increased in both groups after training by 10.4% ± 8.3% and 7.8% ± 4.7% (p < 0.001), respectively. Low-volume maximal isometric leg-press complex training at S-MTU causes angle-specific adaptations in isometric strength and RFD, while dynamic muscle performance is independent of muscle length during training.